Extensive complex neocortical movement topography devolves to simple output following experimental stroke in mice - Wolsh, Cassandra C.; Brown, Rogers Milton; Brown, Andrew R.; Pratt, Gilbert Andrew; Boychuk, Jeffery Allen (Frontiers in Systems Neuroscience, 2023)
The neocortex encodes complex and simple motor outputs in all mammalian species that have been tested. Given that changes in neocortical reorganization (and corresponding corticospinal output) have been implicated in long term motor recovery after stroke injury, there remains a need to understand this biology in order to expedite and optimize clinical care. Here, changes in the neocortical topography of complex and simple movement outputs were evaluated in mice following experimental middle cerebral artery occlusion (MCAo). Neocortical motor output was defined using long-duration parameters of intracortical microstimulation (LD-ICMS) based on area and spatial coordinates of separate motor output types to build upon our recent report in uninjured mice. LD-ICMS test sites that elicited complex (multi-joint) movement, simple (single skeletal joint) movement, as well as co-elicited FORELIMB + HINDLIMB responses were detected and recorded. Forelimb reaching behavior was assessed using the single pellet reaching (SPR) task. At 6 weeks post-surgery, behavioral deficits persisted and neocortical territories for separate movements exhibited differences in neocortical area, and spatial location, and differed between MCAo-Injured animals (i.e., the MCAo group) and Sham-Injured animals (i.e., the Control group). MCAo-Injury reduced neocortical area of complex movements while increasing area of simple movements. Limited effects of injury were detected for spatial coordinates of neocortical movements. Significant positive correlations were detected between final SPR performance and either area of complex retract or area of co-occurring FORELIMB + HINDLIMB sites.